HEALTH FOOD PROGRAM APPLICATIONS WITH MICROSOFT VISUAL BASIC 6.0 FROM PT. KOMPAK INDOPOLA - Satrio Dwi Seto; Drs. Sunarto Usna, MMSi (Jurnal Sistem Informasi, 2003)
Humans are familiar with as a health food supplement to meet the deficiencies in thedaily food and almost all health food ingredients consisting of vitamins and minerals.Health food is not a material change to the daily feed source.Its use is itself balanced by the functions and expenditures. If only someone had asource of food substances that are sufficient, there is no need to consume excesshealth food.Application program created to provide information on health foods PT CompactIndopola. This application is built using Microsoft Visual Basic 6.0 to view thisapplication can be easily understood by the wearer.